Improving Intensive Reading Skills In Indonesian Language Through The Sq3r Strategy In Class VI SD Negeri 021 Tambusai 2016/2017 Academic Year - Sunarti Sunarti (Indonesian Journal of Basic Education, 2021)
This research starts from the problem of intensive reading learning in schools that has not been managed optimally. The teacher does not use the stages in the reading process and has not applied the strategies in the reading learning process so that it has an impact on the low reading skills of students and less involvement of students. The aim of the study is to improve reading skills intensively with the SQ3R strategy (survey, read, recite, review) in Class VI of SD Negeri 021 Tambusai, Rokan Hulu Regency. Research uses a qualitative approach. The type of research chosen is classroom action research (CAR). The subjects in the study were students of class VI Elementary School 021 Tambusai in Rokan Hulu Regency in the first semester of the 2016/2016 academic year with 9 students. The study was conducted in 2 cycles. The research data is collected by observations in the form of observation sheets and then reflected to take action in the next cycle. The results showed that intensive reading learning with the application of the SQ3R strategy could improve the intensive reading skills of students in class VI.